Pointillist expression of dance forms in Ghana - Acquah, Betty (2011)
A thesis submitted to the Department of Painting and Sculpture, Kwame Nkrumah University of Science and Technology, in partial fulfilment of the requirement of the award of Master of Fine Art (MFA) degree in Painting, 2001